2022-RA-973-ESGO Surgical management of early-stage melanoma of the female lower genital tract: a case series. (20th October 2022) - Zarragoitia, Janire; Sanchez-Prieto, Manuel; Fargas, Francesc; Tresserra, Francesc; Baulies, Sonia; Pellise, Maria; Farres, Alba; Fabregas, Rafael
Abstract : Introduction/Background: Vulvar malignant melanoma (VMM) is the second most common subtype of vulvar cancer, accounting for 5–10% of all vulvar cancers. Melanoma of the vagina is very rare, and accounts for less than 3% of all vaginal malignancies. The prognosis is still very poor, although some advances have been achieved in the last years. One of the most significant changes in the management of melanoma of the female lower genital tract has been the development of less invasive surgical techniques that diminish the risk of postoperative morbidity and long-lasting sequelae. Methodology: We review the surgical management of the pathology, based on the comment of three cases with vulvar melanoma and one case of vaginal melanoma treated at our institution. Results: The diagnosis was reached by biopsy. All four patients had a diagnosis of early-stage mucosal melanoma. Wide local excision with adequate margins was performed, without requiring adjuvant treatment. At the same operative time, functional reconstructive surgery was performed for all four patients. Conclusion: Genital melanomas are rare but aggressive tumors. The diagnosis is usually made by biopsy. The revised AJCC staging system is used to diagnose vulvar melanoma. Wide local excision with adequate margins is the main treatment for early-stage primary VMM and vaginal melanoma. Radiation therapy can be helpful as an adjunctive therapy.Given that they are an infrequent tumor and their treatment is complex, management of these cases should be carried out by a multidisciplinary team.